Lipopolysaccharide from the periodontal pathogen Porphyromonas gingivalis prevents apoptosis of HL60-derived neutrophils in vitro - Murray, D A; Wilton, J M A (Infection and immunity, 2003)
Lipopolysaccharide (LPS) from Porphyromonas gingivalis prevented apoptosis of HL60-derived neutrophils, which could not be restored upon the addition of interleukin-10. Signaling of P. gingivalis LPS through Toll-like receptor 2 (TLR2), not TLR4, may account for the inhibiting effect of P. gingivalis LPS on apoptosis and provide a mechanism for the development of destructive periodontal inflammation.